1996
DOI: 10.1074/jbc.271.25.14819
|View full text |Cite
|
Sign up to set email alerts
|

Purification by Ni2+ Affinity Chromatography, and Functional Reconstitution of the Transporter for N-Acetylglucosamine of Escherichia coli

Abstract: The N-acetyl-D-glucosamine transporter (IIGlcNAc) of the bacterial phosphotransferase system couples vectorial translocation to phosphorylation of the transported GlcNAc. IIGlcNAc of Escherichia coli containing a carboxyl-terminal affinity tag of six histidines was purified by Ni2+ chelate affinity chromatography. 4 mg of purified protein was obtained from 10 g (wet weight) of cells. Purified IIGlcNAc was reconstituted into phospholipid vesicles by detergent dialysis and freeze/thaw sonication. IIGlcNAc was or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Mutations in nagE reduce GlcNAc(6P) levels in strains carrying nagA mutations. Another enzyme known to produce GlcNAc6P is the nagE-encoded PTS transporter for GlcNAc (19). Introduction of the nagE mutation together with the nagA mutation (mutant group 5) resulted in an approximately 60% decrease in GlcNAc(6P) levels ( Fig.…”
Section: Vol 191 2009mentioning
confidence: 99%
“…Mutations in nagE reduce GlcNAc(6P) levels in strains carrying nagA mutations. Another enzyme known to produce GlcNAc6P is the nagE-encoded PTS transporter for GlcNAc (19). Introduction of the nagE mutation together with the nagA mutation (mutant group 5) resulted in an approximately 60% decrease in GlcNAc(6P) levels ( Fig.…”
Section: Vol 191 2009mentioning
confidence: 99%
“…Bacterial strains, M13 phage display libraries and media E. coli K-12 strains used were K91 Kan r (Kanamycin) (HfrC thi ), UT580 ⌬(lac-proAB ), supD ; f ЈlacI (Mao et al, 1995), and LR2-168⌬G (pJFEH6) (Mukhija and Erni, 1996). M13 phage display libraries expressing 6-mer, 15-mer and 10-mer inserts in pIII were obtained from J. K. Scott, G. P. Smith and B.…”
Section: Methodsmentioning
confidence: 99%
“…GlcNAc (Mukhija and Erni, 1996). After 30 min at 37ЊC, the reaction was stopped and GlcNAc-6-phosphate was separated from free GlcNAc by anion exchange chromatography on AG-1-X2 (50-100 mesh, Biorad) (Kundig and Roseman, 1971).…”
Section: ¹1mentioning
confidence: 99%
See 1 more Smart Citation
“…There is consequently a need for intracellular phosphorylation (Saier & Schmidt, 1981). In a reconstituted system, Mukhija & Erni (1996) showed that the nonvectorial sugar phosphorylation reaction exhibits about 126 lower affinity for the sugar substrate than the vectorial process, but that the maximal reaction rate for the former process is 2.56 greater than for the latter. Thus, while the cytoplasmic forms of PTS enzymes II clearly can provide the function of nonvectorial phosphorylation, it is also possible that the membrane-integrated forms can catalyse this process.…”
Section: Technique Nature Of Information Obtainedmentioning
confidence: 99%